A study of his analysis between the differential learning method and the imperative method in performing the snatch lift for young adults - Soud Hassan, Hayder (International Journal of Psychosocial Rehabilitation, 2020)
The research aims to study his analysis of the snatch raise between the differential learning method and the commanding method by the junior weightlifting quadruple and to identify the best study between the differential and commanding methods in the performance of the snatch for junior players aged 15-16 years. The researcher hypothesizes that the differential method in the analytical study of Al-Amri’s method in performing the snatch lift in quadruple weightlifting for the junior class at ages 15-16. The researcher used the descriptive method in the manner of the survey method of weightlifting for the junior category (15-16 years) for the two equal groups in order to suit the nature of the research problem. The research sample consisted of 10 players from the Specialized School in Diyala Governorate for Weightlifting, which is based in Al-Khalis Sports Club, and they were chosen from the research community by 100%. Two players and a reconnaissance experiment were conducted to control the work on Sunday, 16/02/2019, for the research sample through the performance of the players for the snatch raise, and the performance evaluation was 10 degrees through three accredited referees in the field of the game, either the main experiment on Tuesday, corresponding to 18/02/2019, at three o’clock in the afternoon, and after identifying the results, the researcher processed them by using the SPSS statistical bag. After analyzing the results, the researcher reached the most important conclusions: through the analysis that was carried out by the referees, the results were in favor of the differential method for the junior weightlifters, and the researcher concluded that the differential method is more exciting and interesting to the research sample than the American method.